Trust-enhanced secure mobile agent-based system design. (6th July 2007) - Foster, David; Varadharajan, Vijay
This paper presents a Security and Trust Enhanced Mobile Agent (SATEMA) architecture. It investigates some of the design decisions encountered during the development of the architecture and its implementation. In particular, we consider design issues such as security and trust policy management, support for multiple applications as well as with single- and multiple-hop scenarios using the proposed architecture. We discuss the design choices and describe the solutions that have been adopted in the architecture. We have implemented two applications, namely, a travel application and an auction application using this proposed SATEMA architecture.